Ekonomi pertanian era pandemi dengan metafora kupu-kupu berkode R12 dan R47 dalam ibadah - Aziz, Roikhan Mochamad (Universitas Muhammadiyah Mataram, 2022)
The aim of this research is to analyze agricultural economic development in the pandemic era with the function of butterflies as agricultural pollinating insects with codes R12 and R47 in symbols of worship. The object of this research is agricultural pollinating insects, namely Butterflies. The research was carried out from literacy studies of journals, books, scriptures, and electronic media. The methodology used is descriptive analysis. The methods used include reflexivity, dynivity, and similarity. The results obtained that the Butterfly motif stores codes R12 and R47 which are the unification of religion and science. There is a natural morphology on the butterfly's upper wings in the form of seven individual lines (7). The bottom wing motif shows a pattern of three (3) small circles like the letter sin, there is also a protrusion of the inner wing that has a long motif with the pattern of the number one (1) like the letter lam, and the largest circle pattern with the number nine (9) on the inside like the letter mim, so it looks like 319 and sinlammim. The source of my reflexivity comes from the R12 which is positioned at the bottom. The number 19 out of 319 is also found in Covid-19 which has an economic impact. The butterfly carries the message of the formula resulting from the structure of creation on the wings with the Hahslm 472319 pattern. This formula gives the meaning of dynivitas (unification) in the Butterfly that religion and science are one unit. Besides that, there is also meaning in the life of a pandemic in the form of a link between the existence of butterflies that the agricultural process is carried out in a worship way through insects with a wing motif which shows that humans turn to God for worship. The novelty of this research is that the dynivtas formula stored in the butterfly's wings can be used as a lesson in agricultural ecosystems in the current pandemic economic era.